A pilot study examining the effectiveness of brief sleep treatment to improve children's emotional and behavioral functioning. Issue 3 (3rd July 2019) - Kidwell, Katherine M.; McGinnis, J. Christopher; Nguyen, Anhthony V.; Arcidiacono, Steven J.; Nelson, Timothy D.
ABSTRACT: This pilot study evaluated a brief sleep treatment for children presenting with emotional/behavioral disorders. Parents of children ages 6 to 11 years ( n = 27) completed measures of emotional/behavioral symptoms at baseline, following sleep treatment, and after behavioral parent training for emotional/behavioral symptoms. Children wore actigraphs to objectively measure sleep, and parents completed weekly assessments of children's symptoms. Emotional/behavioral symptoms improved from baseline to post-sleep treatment and continued to improve following treatment specifically for emotional/behavioral problems. Brief behavioral sleep interventions show promise for improving emotional/behavioral disorders. Future research is needed to evaluate sleep interventions in controlled trials.